Analisis Biaya Pengembangan dan Value-Added Sistem Informasi Akuntansi Pelayanan Rawat Jalan dan Rawat Inap pada Rumah Bersalin dan Klinik Gebang Medika - Hapsari Widyani (NUCLEUS, 2020)
The purpose of this study was to analyze the processes and procedures for accounting information systems for outpatient and inpatient services at Gebang Medika's Maternity Hospital and Clinic. In addition, it is also used to analyze procurement costs and how to create value-added accounting information systems for outpatient and inpatient services at the Maternity Hospital and Gebang Medika Clinic. The data collection method was carried out by direct observation to the research object, namely the Maternity Hospital and the Gebang Medika Clinic. The data used are primary data. This study uses value-added analysis and its design uses a web technology base and MySQL for its database.The results in this study are outpatient and inpatient service procedures at this clinic starting from the patient coming to the clinic then carrying out an examination at the intended polyclinic then being examined and given a copy of the prescription by the doctor. Then a payment receipt will also be given and the patient makes a payment transaction at the cashier and gets a receipt and a copy of the prescription as an introduction to get a medicine. The new project development system will cost IDR 41,877,675 in six months. Looks lower because there is a reduction in the cost of using office stationery. However, if it is calculated within one year, it appears that the costs are quite large because there are analysis and design costs, installation costs, and implementation costs. The added values created include: optimizing the quality of service, increasing the efficiency of service time for patients and making reports, reducing the use of paper and office stationery, increasing internal control, and improving decision making.